The Impact of eWOM and Celebrity Endorsements on Cosmetic Purchase Intentions: Mediated by Brand Image - Fikri Farhan; Wali, Safianti (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
Despite its popularity, Emina, a cosmetic product, has yet to break into the league of top brands. Therefore, this research aims to investigate the factors influencing consumer purchase intention. Specifically, the study examines the direct and mediated effects of electronic word of mouth and celebrity endorsement on purchase intention, with brand image as a mediating factor. The study involved 200 respondents selected through a non-probability sampling method using purposive sampling techniques. Data collection was conducted using a questionnaire distributed via Google Forms. The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the research model, and hypothesis testing was carried out using the Smart PLS version 3.2.9 analysis tool. The findings reveal that electronic word of mouth and celebrity endorsement positively and significantly impact brand image. Electronic word of mouth alone does not influence purchase intention, while celebrity endorsement and brand image positively and significantly affect purchase intention. Furthermore, electronic word of mouth and celebrity endorsement positively and significantly impact purchase intention when mediated by brand image.